The network is your customer : five strategies to thrive in a digital age - Rogers, David L., 1970- (Yale University Press, 2010)
"With clear analysis and practical frameworks, Rogers shows how any organization can apply the five strategies to meet its own key business objectives. He presents a wealth of case studies from numerous business, consumer, and nonprofit categories. And he offers a clear process for planning and implementing a customer network strategy. Whether they sell shoes or news, software or healthcare, any business leaders who want to succeed in our digital age will find the answers they need in this book."--Publisher's description